PENGELOLAAN SANITASI TOILET UMUM DAN ANALISA KANDUNGAN Candida albicans PADA AIR BAK TOILET UMUM DI BEBERAPA PASAR TRADISIONAL KOTA MEDAN TAHUN 2012 - Yeni Hendlyana; Evi Naria; wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2013)
Sanitation management of public toilet and analysis the content of Candida albicans in the tub water of public toilet in some traditional market of Medan city in 2012. Many merchant and visitors influence the need for public toilets. public toilets in Indonesia is inadequate, especially sanitation of public toilet is still far from expected. The bacteria most commonly found in all places in the toilet is a bacteria that normally exist in human skin. Poor sanitation in the toilet will facilitate growth of bacteria, viruses, fungi such as Candida albicans.This study aimed to find a public toilet sanitation management and the existence of Candida albicans in the tub water of public toilet in traditional markets. This studies was descriptive, to describe the management of sanitary toilet in traditional markets and Candida albicans in the tub water in public toilets. Object of this study is sanitary public toilets in traditional markets. In this study, a survey was also conducted on the fungus Candida albicans tubs toilets that are common in some traditional markets. The results showed the Pasar 3 toilet almost all variables meet health requirements established Pasar 1 toilet while the least meet the variable requirements. Management traditional markets toilet all have the operational and financial resources have toilet cleaners. Some traditional market toilet tub drain and clean the toilet at regular intervals in accordance with predetermined. Not found the fungus Candida albicans in the tub water at the four public toilets traditional markets. To the managers should further enhance efforts to manage and improve the behavior of officers by providing training on sanitation sanitation especially in toilets and sanitation facilities complete according to the sanitary standards of public toilets. Key words: Public Toilet, Candida albicans, Sanitation